Kesediaan Pemimpin Agama Muslim dan Kristian dalam Membentuk Keharmonian Agama: Keperluan dan Limitasi: Readiness of Muslim and Christians Leaders in Forming Religious Harmony: Necessity and Limitation - Abdul Rahman, Nur Farhana; Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Religious tolerance was implemented in Malaysia especially in Muslim-Christian relation in various ways by many parties. However, most of the Muslim-Christian’s issues in Malaysia are still pending due to lack of sources in making the decision. Hence, this research is carried out to clarify the phenomenon of religious tolerance from the perspective of Muslim leaders (Mufti) and Christian’s representative leader (Pastors). In depth interview has been carried out among five Muslim’s representative leaders and five representative Christian’s leader. Data from the interviews has been analyzed thematically using Atlas Ti software. The result shows this phenomenon of religious tolerance in Muslim-Christian relation is not denying two things; (i) recognition of religious diversity (ii) willingness to live in harmony. These two main elements then prove that religious tolerance in Muslim-Christian relations have not led to the acceptance of religious pluralism and does not violate the faith of a religion.